PENYULUHAN DAMPAK INFEKSI HIV AIDS KEPADA MASYARAKAT DESA LUMBAN PEA TIMUR, KABUPATEN TOBA - Endy Juli Anto; Dwi L. D. S. Siahaan; Evirosa J. Simanjuntak; Inda M. Sinaga; Faskanita M. Nadapdap; Frengky S. Manullang; Novrina Situmorang; Jimmy Jimmy; Juliyanti Juliyanti; Laura P. S. Tambunan; Widjaya Taufik Tiji; Alex M. Lumbanraja; Jadeny Sinatra; Alexander P. Marpaung; Elizabeth S. Girsang; Ivonne R. V. O Situmeang; Jerry Tobing; Caroline Koswara; Helmida Gultom; Jeffrey (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community Service (PkM) is carried out by the Faculty of Medicine Universitas Methodist Indonesia by providing counselling the effect of HIV Infections and AIDS. PkM was held on 8-11 June 2022 at Lumban Pea Timur, Balige,Toba District, North Sumatera. The method used is to provide counselling/lectures and provide motivation, then followed by question and answer to obtain results and solutions as a form of problem’s solving and obstacles faced. The results of PkM with counselling are very effective considering that there are still many people who do not get information about HIV infections and AIDS. With this counselling, the public becomes aware of the HIV_AIDS Infections problem. Thus, it is hoped that the people of Lumban Pea Timur will aware and know how to prevent their community from HIV-AIDS Infections.